2017
DOI: 10.1111/mec.14113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the early social environment on behavioural and genomic responses to a social challenge in a cooperatively breeding vertebrate

Abstract: The early social environment can have substantial, lifelong effects on vertebrate social behaviour, which can be mediated by developmental plasticity of brain gene expression. Early-life effects can influence immediate behavioural responses towards later-life social challenges and can activate different gene expression responses. However, while genomic responses to social challenges have been reported frequently, how developmental experience influences the shape of these genomic reaction norms remains largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 112 publications
3
61
1
Order By: Relevance
“…Future studies will reveal whether the observed expression differences are also causally related to age‐dependent social behavioural changes during early development, and whether these gene expression differences are transient or permanent. Previous studies in N. pulcher established that the early social environment affects molecular mechanisms of stress regulation much later in life and that the effects on stress axis programming are mediated by an evolutionary conserved molecular pathway in these fish (Nyman et al, , ; Taborsky et al, ). These studies, however, treated molecular processes during the important social experience phase essentially as a black box.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Future studies will reveal whether the observed expression differences are also causally related to age‐dependent social behavioural changes during early development, and whether these gene expression differences are transient or permanent. Previous studies in N. pulcher established that the early social environment affects molecular mechanisms of stress regulation much later in life and that the effects on stress axis programming are mediated by an evolutionary conserved molecular pathway in these fish (Nyman et al, , ; Taborsky et al, ). These studies, however, treated molecular processes during the important social experience phase essentially as a black box.…”
Section: Discussionmentioning
confidence: 99%
“…N. pulcher possess a large and refined repertoire of affiliative, submissive and aggressive social behaviours used to navigate the complexities of their social environment (Taborsky & Oliveira, ), helping to resolve within‐group conflict and to maintain group stability (Taborsky, ; Taborsky & Taborsky, ). The early social environment during the first two months after reaching the fry stage strongly influences the ability to express this behavioural repertoire in an appropriate, context‐specific manner (Arnold & Taborsky, ; Fischer et al, ; Nyman et al, , ; Taborsky et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations